The impact of the name writing skill in preschool children on print knowledge, alphabet knowledge, and phonological awareness: The case of Turkey - Altındağ Kumaş, Özlem; Sümer Dodur, Halime Miray; Yüzbaşıoğlu, Yasemin (Southeast Asia Early Childhood Journal, 2021)
The purpose of this study is to analyze the name writing skills, print knowledge, phonological awareness, and letter knowledge skills of preschool Turkish children of different socioeconomic levels concerning various variables. This study also analyzes the predictiveness of name writing in supporting early literacy skills of children. The study included 357 preschoolers, which were 60 to 72 months old, with a mean age of 64,5 months. Name writing, phonological awareness, print awareness, and alphabet knowledge skills were compared to socioeconomic levels using the MANOVA analysis. The multivariate linear regression analysis was performed to predict the name writing variable using alphabet knowledge, print awareness, and phonological awareness variables of preschool children with different socioeconomic levels. The results of the study pointed to significant differences among all skills concerning socioeconomic status (SES). Low SES children got lower scores in all sub-skills. The study also compared early literacy performances of children based on the educational level of mothers, and significant differences were found among groups in all sub-skills. As the educational level of mothers increased, the scores of children out of all sub skills also increased. Another result got by the study is that the name writing skills of children have a significant predictive effect on print knowledge, alphabet knowledge, and phonological awareness. This study is important as it indicates about the early writing skills in a language like Turkish, which has transparent orthography, and it can pave the way for future research on the subject.